2017
DOI: 10.1177/1040638717717290
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of fatal pneumonia in racehorses

Abstract: Respiratory diseases have a major impact on racehorses in training and are often cited as the second most common reason of horses failing to perform. Cases were submitted by the California Horse Racing Board to the California Animal Health and Food Safety laboratory for postmortem examination between January 1, 2005 and December 31, 2014. We determined the demographics of racehorses with fatal pneumonia, characterized the pathologic findings in animals with a postmortem diagnosis of respiratory infection, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 33 publications
2
29
0
3
Order By: Relevance
“…This condition has been previously described in Brazil in two horses (Panziera et al 2014, Estima-Silva et al 2017, and in this study a suggestive diagnosis of EMPF by EHV-5 in one of the cases was obtained by the association of the gross and the microscopic features. Similarly to the previously described changes in a race horse, the multiple intranuclear inclusion bodies associated to the interstitial fibrosis are characteristic of this condition (Williams et al 2007, Carvallo et al 2017. The histological features of EMPF are distinct from other causes of fibrosis (Williams et al 2007), as it was observed in the remaining two cases of interstitial fibrosis, in which a specific cause could not be determined.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This condition has been previously described in Brazil in two horses (Panziera et al 2014, Estima-Silva et al 2017, and in this study a suggestive diagnosis of EMPF by EHV-5 in one of the cases was obtained by the association of the gross and the microscopic features. Similarly to the previously described changes in a race horse, the multiple intranuclear inclusion bodies associated to the interstitial fibrosis are characteristic of this condition (Williams et al 2007, Carvallo et al 2017. The histological features of EMPF are distinct from other causes of fibrosis (Williams et al 2007), as it was observed in the remaining two cases of interstitial fibrosis, in which a specific cause could not be determined.…”
Section: Discussionsupporting
confidence: 68%
“…When these pathogens are compared, S. equi subsp. zooepidemicus has a broader tissue tropism (Carvallo et al 2017), being able to infect, in addition to the lungs, other reproductive organs (Erol et al 2012). On the other hand, S. equi subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…zooepidemicus eine wichtige Bedeutung zuzukommen scheint [11,12]. Dieser Keim ist sowohl bekannter Kommensale der oberen Atemwege des Pferdes, aber nachweislich auch opportunistischer Erreger bei schweren Infektionen der tiefen Atemwege [13].…”
Section: Primäre Sinusitidenunclassified